The Seven Laws of Teaching for Christian Education - Yemima Handoyo (Universitas Pelita Harapan, 2020)
Ideally that every Christian teacher should follow certain fundamental principles so that the aim of Christian education can be met. And this idea is not just a current modern issue or mere utopian thought but a profound time-tested element. And the basis of those principles should be on Biblical truth. Through ages and centuries, these principles or in other word laws have been conducted by what we know now as classical education. No matter what the subject is, the tools or the strategies that are used in these principles will become the foundation of the teaching to face any challenges within the context of the ever-changing setting. In this essay, the classic work of John Milton Gregory written in the nineteenth century, titled The Seven Law of Teaching will be analyzed by examining its philosophy and biblical theology. From the research that has been done, conclude principles that Gregory brought up as The Seven Laws of Teaching is linear with biblical truth and Christian teachers can rely on this principles as the foundation for shaping and molding their Christian teaching in today world that keep building and reconstructing without a firm foundation.